2017
DOI: 10.1104/pp.17.00361
|View full text |Cite
|
Sign up to set email alerts
|

Night-Break Experiments Shed Light on the Photoperiod1-Mediated Flowering

Abstract: Plants utilize variation in day length (photoperiod) to anticipate seasonal changes. They respond by modulating their growth and development to maximize seed production, which in cereal crops is directly related to yield. In wheat (Triticum aestivum), the acceleration of flowering under long days (LD) is dependent on the light induction of PHOTOPERIOD1 (PPD1) by phytochromes. Under LD, PPD1 activates FLOWERING LOCUS T1 (FT1), a mobile signaling protein that travels from the leaves to the shoot apical meristem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
80
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(95 citation statements)
references
References 56 publications
7
80
0
Order By: Relevance
“…This PPD1 allele has a deletion in its promoter region that encompass the binding site of the ELF3 protein repressor [5], resulting in ectopic expression of PPD1 during the night [14], which is critical for the photoperiodic response as demonstrated in night-break experiments. Induction of PPD1 in the middle of a 16 h night (SD) by a 15 m pulse of light accelerates heading time almost as much as a LD photoperiod [4]. In Brachypodium , it has been proposed that PHYC activation of PPD1 is mediated by ELF3 [5], so the elimination of an ELF3 binding site in the Ppd-A1a allele in wheat may limit the transmission of the phytochrome signal to PPD1 .…”
Section: Discussionmentioning
confidence: 99%
“…This PPD1 allele has a deletion in its promoter region that encompass the binding site of the ELF3 protein repressor [5], resulting in ectopic expression of PPD1 during the night [14], which is critical for the photoperiodic response as demonstrated in night-break experiments. Induction of PPD1 in the middle of a 16 h night (SD) by a 15 m pulse of light accelerates heading time almost as much as a LD photoperiod [4]. In Brachypodium , it has been proposed that PHYC activation of PPD1 is mediated by ELF3 [5], so the elimination of an ELF3 binding site in the Ppd-A1a allele in wheat may limit the transmission of the phytochrome signal to PPD1 .…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were made in the short‐day plants rice and Chrysanthemum, where a night break given in the middle of the night period had the strongest inhibitory effect on the flowering (Horridge and Cockshull , Ishikawa et al ). In long‐day plant wheat, several night breaks were tested and the most successful night break was the one given at the middle of the night period (Pearce et al ). The action of a night break may not be regulated through coincidence between StCOL1 and light, but through a mechanism involving the night length.…”
Section: Discussionmentioning
confidence: 99%
“…Although StCOL1 was expressed at a low level during a classic night break, StSP5G was induced and tuberization was repressed. In wheat, the greatest night‐break‐mediated flower induction was observed in the middle of the night when PPD1 expression was low (Pearce et al ). The authors suggested one or more unknown circadian clock genes gated the night‐break effect, which may be the case for potato as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A night break not only inhibits short-day tuberization, but also short-day flowering in species like Chrysanthemum (Borthwick and Cathey, 1962, Horridge and Cockshull, 1989, Higuchi et al, 2012. Furthermore, night breaks given in the long nights of a short day can induce flowering in long-day plants like wheat (Pearce et al, 2017). Although a lot of research has been done on night breaks, it is not fully understood how a night break regulates tuberization.…”
Section: Resultsmentioning
confidence: 99%